ANTARES: A gateway to ZTF and LSST alerts. Issue Volume 15:Issue S357(2019) (October 2019) - Lee, Chien-Hsiu; Soraisam, Monika; Narayan, Gautham; Matheson, Thomas; Saha, Abhijit; Stubens, Carl; Wolf, Nicholas
Abstract: Studies of white dwarfs have greatly benefited from time-domain surveys and subsequent follow-up observations. However, with the avalanche of alerts delivered by ZTF and LSST and the limited resources for follow-up, we will need brokers to select intriguing alerts that warrant follow-up in a timely manner. At the University of Arizona and NSF's OIR Lab, we are developing the Arizona-NOAO Temporal Analysis and Response to Events System, to hunt for the rarest of the rare events in the time-domain. In this work, we provide an overview of the ANTARES system, how we use ZTF as a training set, and the way forwards to LSST.